Detection of Lateralized Readiness Potential using Emotiv EPOC - Bártík, Radovan (2015)
Emotiv EPOC is a low-cost consumer headset capable of acquiring a raw EEG signal. The thesis evaluates its usage for an acquisition of research event-related potentials. A controlled laboratory experiment was performed with an objective of isolating the Bereitschaftspotential (Readiness Potential) and other movement-related potentials and comparing the results with the results of the previous research. The possibility of measuring the potential with Emotiv EPOC was not confirmed, most probably due to procedural issues during the experiment, however, further analysis of the data suggests its presence. Other outcomes of the research include qualitative findings about the headset, mainly its hardware construction, and testing feedback of EEGLab, an open source toolbox for EEG processing and visualization.